Rethinking connectedness : an investigation into the access of teacher professional learning in regional and remote Western Australia - Broadley, Tania Lee (Curtin University, 2011)
Many teachers working in remote and regional areas have limited access to collegial support networks. This research aimed to examine the existing strategies that were being undertaken by the Department of Education in Western Australia, to provide professional learning to teachers in regional and remote areas. It was important to establish the perceptions of teachers’ access to professional learning from those working at the coalface in geographically dispersed areas. Consequently, the possible opportunity for improving the amount and variety of professional learning, through the application of both synchronous and asynchronous technologies was proposed. The study was guided by the primary research question: “In what ways might technology be used to support professional development of regional and remote teachers in Western Australia?” Generating descriptions of current practice of professional learning along with the teacher perceptions were central to this research endeavour.The study relied on a mixed method research approach in order to attend to the research question. The data were collected in phases, referred to as an explanatory mixed methods design. Quantitative data were collected from 104 participants to provide a general picture of the research problem. To further refine this general picture, qualitative data were collected through interviews and e-interviews of 10 teachers. Participants in the study included graduate teachers, teachers who had taught more than two years, senior teachers and Level Three teachers from seven teaching districts within Western Australia. An investigation into current practice was included in this phase and technologies available to support a professional learning community over distance were documented. The final phase incorporated the formulation of a conceptual framework where a model was developed to facilitate the successful implementation of a professional learning community through the application of synchronous and asynchronous technologies.The study has identified that travel time in order to access professional development is significant and impacts on teachers’ personal time. There are limited relief teachers available in these isolated areas which impacts on the opportunities to access professional development. Teachers face inequities, in terms of promotion, because professional development is explicitly linked to promotional opportunities. Importantly, it was found that professional learning communities are valued, but are often limited by small staff numbers at the geographic locality of the school. Teachers preferred to undertake professional learning in the local context of their district, school or classroom and this professional learning must be established at the need of the individual teacher in line with the school priorities. Teachers reported they were confident in using technology and accessing professional development online if required, however, much uncertainty surrounded the use of web 2.0 technologies for this purpose. The recommendations made from the study are intended to identify how a professional learning community might be enhanced through synchronous and asynchronous technologies.